2000
DOI: 10.1039/a908985c
|View full text |Cite
|
Sign up to set email alerts
|

Chiral and achiral platinum(II) complexes for potential use as chemotherapeutic agents: crystal and molecular structures of cis-[Pt(L1)2] and [Pt(L1)Cl(MPSO)] [HL1 = N,N-diethyl-N ′-benzoylthiourea]

Abstract: Chiral and achiral platinum(II) complexes for potential use as chemotherapeutic agents: crystal and molecular structures of cis-[Pt(L 1 ) 2 ] and [Pt(L 1 )Cl(MPSO)] [HL 1 ‫؍‬ N,N-diethyl-NЈbenzoylthiourea]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 18 publications
2
35
1
1
Order By: Relevance
“…Some of them are employed as fungicidal, antiviral, antimicrobial [10], parasiticidal [11], antitumoral [12] and pesticidal agent [13][14][15]. Indeed cytotoxicity studies using HeLa cancer cell lines have demonstrated that some of these platinum acyl thioureas show cytotoxic behavior, with the antiproliferative effects being dependent on the nature/type of the substituent in the acyl thiourea ligand [16][17][18]. Having this in mind our research group has been interested in developing new thiosemicarbazones or similar ligands, including polydentate ones such as acyl thioureas, containing N, S and O atoms with the capacity to form transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are employed as fungicidal, antiviral, antimicrobial [10], parasiticidal [11], antitumoral [12] and pesticidal agent [13][14][15]. Indeed cytotoxicity studies using HeLa cancer cell lines have demonstrated that some of these platinum acyl thioureas show cytotoxic behavior, with the antiproliferative effects being dependent on the nature/type of the substituent in the acyl thiourea ligand [16][17][18]. Having this in mind our research group has been interested in developing new thiosemicarbazones or similar ligands, including polydentate ones such as acyl thioureas, containing N, S and O atoms with the capacity to form transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Single enantiomeric drugs used in recent years constitutes > 30% of total therapeutic drugs [5] [6]. The structure -function relationship in nature is so powerful that, when a functional disorder is manifested in the form of a disease, it can be handled in many cases only by using a molecule of specific chiral structure [7]. Thus, the introduction of chirality enhances selective binding of the complexes to molecular targets.…”
mentioning
confidence: 99%
“…In the complexes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) there are two coordinated triphenylphosphine ligands, in cis position, according to the 31 P{ 1 H} NMR data, and their molar conductivities show that the complexes are cationic species. 39 The NMR ( 1 H and 13 C{ 1 H}) spectroscopy was used to speculate about the molecular structures of the complexes, and a comparative analysis on the basis of the spectroscopic data corresponding to both, free and coordinated ligands with the metallic ion, was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The N,N-disubstituted-N'-acylthiourea ligands L (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) used in this work were synthesized by the procedure previously reported, and the identity of the products was confirmed by comparing their 1 H and 13 C{ 1 H} NMR data with those reported in the literature. 21 The groups R1 and R2 of the ligands are shown in Figure 1.…”
Section: Syntheses Of Nn-disubstituted-n'-acylthioureasmentioning
confidence: 99%
See 1 more Smart Citation